2022
DOI: 10.4081/jphr.2021.2223
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice of Healthy Eating among Public School Teachers in Kuwait

Abstract: Background: Healthy food is essential for strengthening the body and protecting it from diseases. Conversely, unhealthy food can cause severe diseases in children and adolescents. The present study aimed to assess the level of knowledge, attitude, and practice among teachers about healthy food and to examine the associated factors.Design and methods: A cross-sectional study was conducted using a questionnaire distributed to 300 teachers in the Hawalli and Al-Jahra educational areas in Kuwait over approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Participants in this sample performed above average in terms of their perceptions (knowledge, attitude, and practice) of healthy food choices. These results were similar to the findings reported by Kana' An et al (2022) and Mailinda and Lestari, (2019) in Indonesia; the authors found that participants reported positive knowledge, attitude, and practice about healthy food choices. A study was conducted by Farivar et al (2009) to assess Iranian urban household food knowledge, attitude, and practice about healthy food choices.…”
Section: Discussionsupporting
confidence: 90%
“…Participants in this sample performed above average in terms of their perceptions (knowledge, attitude, and practice) of healthy food choices. These results were similar to the findings reported by Kana' An et al (2022) and Mailinda and Lestari, (2019) in Indonesia; the authors found that participants reported positive knowledge, attitude, and practice about healthy food choices. A study was conducted by Farivar et al (2009) to assess Iranian urban household food knowledge, attitude, and practice about healthy food choices.…”
Section: Discussionsupporting
confidence: 90%
“…Several research studies have explored the effects of enhancing knowledge, attitudes, and practices (KAP) alongside improving nutrition outcomes in different contexts. Zeinab et al 2020) conducted a study on schoolteachers in Kuwait (33). These studies all clearly demonstrated the importance of KAP for improving nutritional outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(WHO, 2013) children are guided by meeting physical and psychosocial needs. Nutrition concerns during childhood relate to growth and development needs for positive health (FAO, 2007) Naeeni et al., (2014) evaluated the nutritional knowledge, practice, and dietary habits of primary school and junior high school students in Isfahan province. Also explored crucial differences regarding gender and living governorate of the above-mentioned population in Iran.…”
Section: )mentioning
confidence: 99%
“…Kana ''An et al, (2022) assessed the level of knowledge, attitude, and practice among teachers about healthy food and to examine the associated factors. The study results showed limited knowledge combined with a low level of positive attitude.…”
Section: )mentioning
confidence: 99%